MANAGEMENT OF INNOVATIVE ACTIVITIES IN SERVICE ENTERPRISES AND STRATEGIES FOR ENHANCING COMPETITIVENESS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article analyzes the importance of innovative approaches and management strategies in increasing the competitiveness of service enterprises. It examines the impact of service sector growth, increased investment volume, and the implementation of digital technologies and automation on economic development. The research results highlight the significance of innovative management strategies, competitive advantages, and technological modernization for the sustainable development of the service sector.